Konsep TASBIH: Jembatan Antara Ekspektasi dan Realita Marketer Syari’ah dalam Mencapai Target - Arista fauzi kartika (ITB AAS INDONESIA Surakarta, 2021)
This paper is to determine the expectations and realize of marketers sharia when selling of Islamic banking products. Which is expected to keep holding on to the principles of Islam to achieve the target given to marketers sharia as the amanah of Islamic banks to benefit apart from the material as money, as well as immaterial, as the pleasure of Allah, gratitude, blessings sustenance, etc. Then used the concept TASBIH (Tazkiyah, Amanah, Silaturahmi, Binniyat, Ikhtiar, and Harta) to be able to align to the affairs of the world and the hereafter.